Operational effectiveness of the information technology function in business process change: A case study in a financial services firm - Ball, Richard (Department of Mechanical Engineering, 2017)
In order to address the need to remain flexible in dynamic business environments, organisations must focus on the effectiveness of their core operational processes. The importance of operational effectiveness has been claimed to have a direct influence on business performance. In order to improve their effectiveness, many organisations invest in information technology (IT) systems, even though the extent to which these technological initiatives influence operational effectiveness is considered to be largely misunderstood by the organisations who employ them. In this dissertation, the relationship between the Operations and IT departments of a financial services firm is investigated. This study pays particular attention to the factors that have the potential to influence the ability of the organisation to align its strategies. This enquiry takes the form of two distinct research questions: 1) What factors in the organisation have an impact on the success of business process change proposals? 2) How is the role of IT perceived in the preparation of business process change initiatives? The study involved conducting semi-structured interviews with members of both departments. A qualitative inductive approach was used to analyse the data collected from these interviews in order to identify themes. The emergent phenomena were then considered in conjunction with the literature on organisational effectiveness and strategic alignment, in order to develop a theory that answers the research questions. The findings of the theory that developed resulted in four main relationships. They were: how understanding business processes contributes to improved service delivery; how important communication is in contributing to organisational performance; how effective planning has an impact on product complexity; and the impact that effective organisational planning has on the relationship between IT and operations. The results of this study showed that although there was intention to improve alignment between business and IT strategies, with some noteworthy initiatives emerging, there have been a number of factors inhibiting successful alignment. Some of these factors include: a lack of trust in IT solution delivery, IT remaining ignorant to the impact of process changes, the inability to effectively allocate the business analysis function to the correct change proposals, and the silos of process knowledge that exist within operations. The recommendations of this study include: improvements to the visibility of business processes; methods to improve knowledge sharing; and strengthening the focus of the business analysis function.